2018
DOI: 10.1016/j.jsams.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal training injury prevention in the U.S. Army: Evolution of the science and the public health approach

Abstract: Injuries cause more morbidity among soldiers in the U.S. Army than any other health condition. Over two-thirds of U.S. soldiers' injuries occur gradually from cumulative micro-traumatic damage to the musculoskeletal system as a result of physical training activities. Paradoxically, the very physical training activities required to improve soldier performance also result in injury. Determining the amounts and types of physical training that maximize performance while minimizing injuries requires scientific evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…Overall GH is known to stimulate growth in children and adolescents with various metabolic functions [112]. Musculoskeletal injuries represent a major public health problem [113], and medications improve muscle repair and restore functions. Increasing IGF-1 levels improves SM recovery after myotoxic injury and the administration of IGF-1 has the potential for accelerating healing after trauma [114].…”
Section: Interaction Between Igf-1 and Igf-1rmentioning
confidence: 99%
“…Overall GH is known to stimulate growth in children and adolescents with various metabolic functions [112]. Musculoskeletal injuries represent a major public health problem [113], and medications improve muscle repair and restore functions. Increasing IGF-1 levels improves SM recovery after myotoxic injury and the administration of IGF-1 has the potential for accelerating healing after trauma [114].…”
Section: Interaction Between Igf-1 and Igf-1rmentioning
confidence: 99%
“…Injuries are commonly cited as a leading health problem among civilians, [1][2][3][4] workers, 1,5 athletes, [6][7][8] and military populations. [9][10][11][12][13] Injury has conceptually been defined as bodily damage caused by transfers of energy or the absence of energy. 2,[14][15][16] In theory, this is broadly inclusive of a vast array of outcomes (types of bodily damage) and countless causal activities or events (e.g., vehicle crashes, falls, sports and exercise, occupational tasks, intentional violence, environmental or weather-related conditions, and poisonings).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Yet U.S. Army medical surveillance and investigative studies have shown that these severe incidents are not representative of the entire military injury problem. [11][12][13]19 Military studies in the U.S. [19][20][21][22] and several international countries [23][24][25] have indicated that injuries with greatest adverse impact to military readiness are musculoskeletal injuries (MSKI). MSKI refers to damage to bone, muscle, tendon, ligaments, joints, cartilage, bursa, or synovium caused by either sudden trauma (e.g., fractures, dislocations, sprain, strains, etc) or by the accumulation of repeated microtrauma (e.g., stress fractures, Achilles tendinopathy, patellofemoral pain and "runner's knee," and dorsalgia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of musculoskeletal injuries (MSKIs) on military medical costs, limited duty days, and military readiness has been well-documented. 11 , 12 , 20 Cases of MSKI were responsible for >75% of all medically nondeployable classifications in 2015. 2 In addition to the impact on active-duty military members, initial-entry training MSKIs are financially burdensome, particularly if training is prolonged or trainees are discharged due to injury.…”
mentioning
confidence: 99%